Mapping Brussels' Displaced Housing Ecosystem: Palais des Droits’ Post-Eviction Geographies and “Weird Alliances” - Nagi, Tasneem (2024)
As displaced people arrive at European cities, the experiences of displacement caused by forces of bordering and securitization do not end at the point of arrival. Due to a pre-existing housing crisis characterized by critical shortages in affordable housing, a series of urban displacements ensue. The intersectionality between the border regime and neoliberal housing systems produces gaps in migrant housing needs which neither the reception nor the housing governance adequately addresses. In this vacuum, moments of encounter between displaced migrants and non-migrants, who share a need for housing, can be witnessed in the limited affordable urban space where they attempt to address their own precarity. Through stories from housing struggles in Brussels, this article maps what we term a “displaced housing ecosystem” through the geographies and alliances that emerge along the trajectory after the eviction of Palais des Droits. Here, migrants and non-migrants come together and employ various tools, ranging from (political) occupations of vacant buildings to inventive ad hoc partnerships with state and non-state actors towards the provision of housing and other hospitality infrastructures. Building on Lancione’s notion of “weird exoskeletons,” the article aims to map such constellations. By focusing on infrastructural objects that reflect the emerging non-conventional alliances to respond to displacement, narrating the solidarities as well as antagonisms within them, the article sheds light on displaced housing governances from below. The purpose is to highlight the diverse and hybrid forms of actions, actors, and coalitions constituting an ecosystem for housing displaced migrants, shortly “displaced housing,” in relation to and beyond formal reception and housing systems.